A Voltage-sensorless Current Control of Grid-connected Inverter Using Frequency-adaptive Observer. Issue 4 (2019) - Tran, Thuy Vi; Kim, Kyeong-Hwa
Abstract: This paper presents a grid voltage-sensorless current control design based on the linear quadratic regulator (LQR) approach for an LCL-filtered grid-connected inverter. The proposed scheme relies only on the information from the grid-side current sensors to implement the control algorithm as well as to synchronize the inverter system with the utility grid. Basically, the construction of current controller consists of a full-state feedback regulator augmented with an integral control term for achieving control objectives, and a frequency-adaptive observer to estimate the system state variables and grid voltage parameters even under a non-ideal grid environment with frequency variation. A systematic design method based on the LQR approach is introduced to obtain optimal gains for the controller as well as the adaptive observer. The effectiveness of the proposed scheme is validated through the simulation results.